2015
DOI: 10.1038/srep08967
|View full text |Cite
|
Sign up to set email alerts
|

Atomic interaction mechanism for designing the interface of W/Zr-based bulk metallic glass composites

Abstract: The interaction between active element Zr and W damages the W fibers and the interface and decreases the mechanical properties, especially the tensile strength of the W fibers reinforced Zr-based bulk metallic glass composites (BMGCs). From the viewpoint of atomic interaction, the W-Zr interaction can be restrained by adding minor elements that have stronger interaction with W into the alloy. The calculation about atomic interaction energy indicates that Ta and Nb preferred to segregate on the W substrate surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Therefore, we expand ψ and ν in Π ψ n (S) and p and q in Π p n (S) and require the residual of Eqs. (22) and (23) to be orthogonal to Π ψ n (S) × Π p n (S). This leads to the Galerkin scheme…”
Section: A (Vector) Spherical Harmonics Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we expand ψ and ν in Π ψ n (S) and p and q in Π p n (S) and require the residual of Eqs. (22) and (23) to be orthogonal to Π ψ n (S) × Π p n (S). This leads to the Galerkin scheme…”
Section: A (Vector) Spherical Harmonics Expansionmentioning
confidence: 99%
“…Self-propelled particles can also be confined to a compact manifold like a sphere, as realized by multicellular spherical Volvox colonies [17], bacteria moving on oil drops [18] or layered in water drops [19], or by active nematic vesicles [20]. This has triggered recent theoretical and simulation work on self-propelled particles on spheres considering both their individual [21,22] and collective [23,24] dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Vicsek model, [8] a minimal model to depict the phase transition, has been extended in various aspects since its appearance, such as from polar to apolar particles, [10,11] from intrinsic scalar noise to vectorial noise, [9] and extensions of interactions to include, e.g., cohesion [12] and disordered environments. [14,15] One particular kind of variants is to change the space where SSPs reside from two-dimensional Euclidean space to lattices [16,17] or general manifolds [18] and/or from continuous directional space to discrete ones. [19,20] In Vicsek model and its variants, it is long accepted that the collective motion is optimized with vanishing noise and maximal particle density.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the interface plays an important role in the mechanical properties of composites [22]. Wang et al [23] and Li et al [24] optimized the interface between the metallic glass matrix and the tungsten fiber by adding alloy element to the glass matrix, which significantly increased the compressive mechanical properties of BMGCs. Besides the interface, Conner et al [8] and Dragoi et al [25] found that the thermal residual stresses also influenced the mechanical properties and deformation behaviors of the BMGCs.…”
Section: Introductionmentioning
confidence: 99%